Representasi Kekerasan dalam Film The Big 4 - Pratama, Dimas Sopian; Baksin, Askurifai (Bandung Conference Series: Public Relations, 2024)
Abstract. In the era of the growth of the entertainment industry, the representation of violence in films is a critical concern that requires in-depth understanding. The theme of violence is raised in the context of research to increase understanding of the impact of violence in the media on society. This study reviews the depiction of violence as a central element in the film "The Big 4" with the aim of exploring the representation of violence shown in the film. Carrying the action-comedy genre, the movie "The Big 4" provides a tense, awe-inspiring, and entertaining experience at the same time. A qualitative research method with John Fiske's semiotic analysis approach is used to explore the television codes contained in each scene of violence. The identification of television codes in violent scenes became the focus of the research, and the results were analyzed using John Fiske's "The Codes of Television" theory. In-depth analysis was conducted on the use of levels of reality, representation of violence in various forms, ideological implications in conflict, ideological duality, causes and effects of violence, and the role of violence in character empowerment. The results highlight the complexity of human beings, ideological conflicts, and the impact of violence on characters and society. The movie is not only a work of entertainment, but also an object of research that stimulates critical thinking and reflection in the audience. Abstrak. Dalam era pertumbuhan industri hiburan, representasi kekerasan dalam film menjadi sorotan kritis yang memerlukan pemahaman mendalam. Tema kekerasan diangkat dalam konteks penelitian untuk meningkatkan pemahaman mengenai dampak kekerasan dalam media terhadap masyarakat. Penelitian ini mengulas penggambaran kekerasan sebagai elemen sentral dalam film "The Big 4" dengan tujuan untuk menggali representasi kekerasan yang ditayangkan dalam film. Mengusung genre aksi-komedi, film “The Big 4” memberikan pengalaman tegang, kagum, sekaligus terhibur dalam satu waktu. Metode penelitian kualitatif dengan pendekatan analisis semiotika John Fiske digunakan untuk mengeksplorasi kode-kode televisi yang terkandung dalam setiap adegan kekerasan. Identifikasi kode-kode televisi dalam adegan kekerasan menjadi fokus penelitian, dan hasilnya dianalisis menggunakan teori "The Codes of Television" dari John Fiske. Analisis mendalam dilakukan terhadap penggunaan level realitas, representasi kekerasan dalam berbagai bentuk, implikasi ideologis dalam konflik, dualitas ideologi, penyebab dan dampak kekerasan, serta peran kekerasan dalam pemberdayaan karakter. Hasil penelitian menyoroti kompleksitas manusia, konflik ideologis, dan dampak kekerasan pada karakter dan masyarakat. Film ini tidak hanya menjadi karya hiburan, melainkan juga objek penelitian yang merangsang pemikiran kritis dan refleksi pada penonton.